A highly photoconductive composite prepared by incorporating polyoxometalate into perovskite for photodetection application. Issue 16 (28th January 2016) - Zhang, Yuzhuo; Tao, Ran; Zhao, Xuemin; Sun, Zhixia; Wang, Yanju; Xu, Lin
Abstract : The perovskite–polyoxometalate composite displayed better photoconductivity and photodetction performance than pristine perovskite. Abstract : A photoconductive perovskite–polyoxometalate composite was prepared for the first time by a facile low-temperature and solution-processed method, and this composite exhibited a significantly enhanced photoconductivity and photodetection performance due to introduction of polyoxometalate into the perovskite for fine energy-level matching and efficient charge transfer.